Reconfigurable Mechanical Anisotropy in Self‐Assembled Magnetic Superstructures. Issue 8 (15th February 2021) - Håkonsen, Verner; Singh, Gurvinder; De Toro, José A.; Normile, Peter S.; Wahlström, Erik; He, Jianying; Zhang, Zhiliang
Abstract: Enhancement of mechanical properties in self‐assembled superstructures of magnetic nanoparticles is a new emerging aspect of their remarkable collective behavior. However, how magnetic interactions modulate mechanical properties is, to date, not fully understood. Through a comprehensive Monte Carlo investigation, this study demonstrates how the mechanical properties of self‐assembled magnetic nanocubes can be controlled intrinsically by the nanoparticle magnetocrystalline anisotropy (MA), as well as by the superstructure shape anisotropy, without any need for changes in structural design (i.e., nanoparticle size, shape, and packing arrangement). A low MA‐to‐dipolar energy ratio, as found in iron oxide and permalloy systems, favors isotropic mechanical superstructure stabilization, whereas a high ratio yields magnetically blocked nanoparticle macrospins which can give rise to metastable superferromagnetism, as expected in cobalt ferrite simple cubic supercrystals. Such full parallel alignment of the particle moments is shown to induce mechanical anisotropy, where the superior high‐strength axis can be remotely reconfigured by means of an applied magnetic field. The new concepts developed here pave the way for the experimental realization of smart magneto‐micromechanical systems (based, e.g., on the permanent super‐magnetostriction effect illustrated here) and inspire new design rules for applied functional materials. Abstract : The emergence and control of mechanical anisotropy from magnetic anisotropy is demonstrated in self‐assembled magnetic superstructures of nanocubes. Hard magnetic nanoparticles can yield metastable superferromagnetic alignment which gives rise to reversible reconfigurability of the strong mechanical axis by means of an applied magnetic field. The discovery of the "super‐magnetostriction" effect further strengthens the multifunctional aspect of these attractive materials.